Urban climate forecasts: From risk to resilience. Milan Innovation District's key design aspects for buildings and infrastructures - Boschi, Nadia (Frontiers in Climate, 2023)
Climate-related transitional and physical risks are interrelated. This paper focuses on physical risk as mitigated and embedded into the design of buildings and infrastructures at the Milan Innovation District (MIND). MIND is a development piloting the transition to resilient green urban planning. This paper discusses the methodology adopted to assess the local climate change risks and impacts to be mitigated at the early stages of urban and building design. Climate forecasting modeled two scenarios 4.5 and 8.5 Representative Concentration Pathways (RCP) in 2090. Milan’s climate projections are from the World Bank Change Knowledge Portal and the projected .epw Weatherfiles for Milano Linate. These were generated using IES and Weathershift tool. Results, depending on the selected forecast, indicated up to 3-7⁰C temperatures, up to 10-20% probability of heat waves, up to 12-24% increase in the 24h max precipitation, and up to 8-15% increase in the 5 days max cumulative scenario. The analysis concentrates on the temperature raise including the masterplan sunlight analysis, the spatial thermal comfort analysis, and the climate change visualization. Results were discussed in climate change adaptation and resilience planning workshops with a broad range of stakeholders to identify key strategies and functional distribution de-risking strategies. Resiliency and decarbonization priorities may differ by region. Although, climate change is a material risk for urban development and MIND proves that early stages decisions are essential for adequate mitigation of climate risk, and work with wider industry and government is necessary to respond to the challenge.